Integrasi Nilai Pancasila dan Kerangka Konstitusional dalam Falsafah Pendidikan Nasional Indonesia - Muhaemin, Muhaemin; Sirozi, M.; Abdurrahmansyah, Abdurrahmansyah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This article aims to analyze the integration of Pancasila values and the constitutional framework as the foundation of Indonesia’s national educational philosophy. The study employs a qualitative method using a library research approach through the analysis of normative documents, statutory regulations, and relevant scholarly literature. The data sources include normative documents such as the 1945 Constitution of the Republic of Indonesia, the National Education System Act, educational regulations, academic books, and reputable scientific journals. Data analysis is conducted qualitatively through content analysis, normative interpretation, and conceptual synthesis to examine the integration of Pancasila values within the constitutional framework of national education. The findings indicate that the values of Pancasila elief in God, humanity, unity, democracy, and social justice have been conceptually integrated into the goals, functions, and principles of national education as mandated by the 1945 Constitution and the National Education System Act. This constitutional framework emphasizes that education is not solely oriented toward intellectual development but also toward the formation of character, morality, and social responsibility among learners. Therefore, the integration of Pancasila values and the constitution serves as a crucial foundation for realizing a national education system that is character-based, equitable, and sustainable.